2005
DOI: 10.1007/s10562-005-5868-0
|View full text |Cite
|
Sign up to set email alerts
|

Comments on the characterisation of oxidation catalysts using TPR/TPO

Abstract: Temperature programmed reduction (TPR) and oxidation (TPO) are used extensively in catalyst characterisation. In this paper, we examine the use of TPR/TPO cycles for the characterisation of a range of molybdates and single oxides. In particular we observe that the first cycle differs from that of subsequent analyses, even when the maximum temperature is limited to that used in the catalytic reaction. The effect is independent of heating rates and cooling atmospheres and has been demonstrated using different be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Song et al [16] recently examined the use of TPR/TPO cycles for the characterization of a range of molybdates including BiMoO 6 , CoMoO x , CoBiMoO x and BiMo 12 Fe 2 NiCo 7 MgSb 0.9 Ti 0.1 Te 0.02 O x and single oxides MoO 3 , Bi 2 O 3 and Co 3 O 4 . The results of this investigation demonstrated that for complex molybdates, and also less complex materials, the first and subsequent TPR/TPO cycles are clearly different, the first cycle being unique.…”
Section: A Bulkoxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Song et al [16] recently examined the use of TPR/TPO cycles for the characterization of a range of molybdates including BiMoO 6 , CoMoO x , CoBiMoO x and BiMo 12 Fe 2 NiCo 7 MgSb 0.9 Ti 0.1 Te 0.02 O x and single oxides MoO 3 , Bi 2 O 3 and Co 3 O 4 . The results of this investigation demonstrated that for complex molybdates, and also less complex materials, the first and subsequent TPR/TPO cycles are clearly different, the first cycle being unique.…”
Section: A Bulkoxidesmentioning
confidence: 99%
“…Fig 16. H 2 consumption and H 2 O evolution profiles measured during H 2 temperature-programmed reduction of a passivated Mo nitride (4 m 2 g −1 ) (adapted from Ref [101]…”
mentioning
confidence: 99%